Palatalização de oclusivas alveolares em Sergipe - Souza, Gládisson Garcia Aragão (2016)
The variation in the realization of phonemes /t/ and /d/ has been the subject of several studies in Brazilian Portuguese HORA, 1990; ABAURRE; PAGOTTO, 2002; PAULA, 2006; BATTISTI et al, 2007; PIRES, 2007; DUTRA, 2007; MATTÉ, 2009; SOUZA NETO, 2014, among others), that signal to diatopic conditioning phenomenon. This work aims to contribute to the description of the variety of speech of Sergipe. considering phonetic-phonological aspects of three language communities of the state of Sergipe. Therefore, let us take as an object of study the variation of the consonants /t/ and /d/ before the high front vowel not rounded /i/, which are produced as palate-alveolar affricates (/t/ e /d/) as [‘tia], [‘dent], [ci’dad], [i’dad] produced by informants of Aracaju, Itabaiana and lizard. For this study, 60 were taken sociolinguistic interviews of university's of Falares Sergipanos. The research builds on the Theory of Sociolinguistics variationist (LABOV, [1972]; 2008), and the Usage-Based Phonology (Bybee, 2001). ). For Labov, the language is assumed heterogeneous, conditional upon restrictions with regard to the linguistic context and social context. According to the Usage-Based Phonology, sound changes are phonetically and lexically gradual. The in-memory representation of individuals is affected by the tokens; the language goes through several reorganizations and changes according to the experiences and use. In the refers the process of varying the palatalization, that undergoes adjustments of phonetic properties and articulatory gestures. As results, the statistical selection referring to linguistic and extralinguistic variables in the order of relevance in conditioning was: Geographical Group, Context Phonological Precedent; Sex / Gender; Interviewer; sonority; and Position of Syllable Tonic. The geographic group is that most favors the palatalization of alveolar stops: Aracaju and Itabaiana were the most favored palatalization, which shows the variation diatopic. The consonant sibilant is the factor of the antecedent phonological context that most favors the palatalization of alveolar plosives consonant. As for the Sex / Gender, women palatalizaram more often than men, whereas women tend to use the prestige variant, it is possible to infer that women are leading change. The variable interviewer, this does not favor the trigger effect once the interviewer not palatalizam appear more enhancers of palatalization. And as the variable sound, the deaf factor was the most motivated palatalization in geographical groups analyzed. In both wheels this factor was more motivating for palatalization. And the position of the stressed syllable, expressed more favorable application of the palatalization of dental plosives not end postonic and pretonic. Data from the acoustic analysis revealed the existence of gradients between the production of the full form and the innovative pattern, suggesting a change in progress.